EP751 Cancer in the elderly: do we treat them in the same way?. (1st November 2019) - Sá, I; Ana Carolina, R; Raposo, S; Sousa, R; Correia, P; Aldinhas, P; Castelo Branco, E; Coelho, C; Baltar, V; Sá, L
Abstract : Introduction/Background: The increase of life expectancy is leading to an intensification of number of cancers in older populations. These patients should be managed according to their health status and not only to their age. The aim of this study was to analyse the incidence of cancer in women older than 80 yrs and its impact on survival. Methodology: A retrospective study was conducted, including 177 patients over 80 yrs, referred to our department with gynaecological cancer, between 2013–2018, (6, 6% of total cases referred in the same period). We collected data about oncological disease, including stage, treatment modalities, disease related survival and mortality. Results: The average age was 83 yrs: 70, 0% <85 yrs; 22, 1% between 85–90 yrs and 7, 8% >90 yrs. The most frequent cancers were breast cancer (59, 9%) and endometrial cancer (17, 1%). The other cases were cervical (7, 8%), vulvar (7, 4%) and ovarian cancer (5, 5%), 1 vaginal and 1 tubar cancer. For breast and endometrial cancer, the most frequent stages were stage II and stage IB, respectively. 63, 1% of the patients had surgery as a primary treatment; 5, 5% had neodjuvant treatment, 51, 6% had adjuvant treatment and 26, 3% were directed to palliative care. 16 women had recurrent disease. 18, 8% died from oncologic disease and 8, 9% died from others causes. There were not statistically significant differences in mortality among the age groups (p=0, 98). Conclusion: A high number of cancer cases was observed in older women. Although there is no standard of care for elderly patients, advanced age shouldn't be considered a limitation to treatment. Surgery is an important treatment modality in these age groups, who sometimes haven't conditions for systemic treatment. Disclosure: Nothing to disclose.